(NsTOHASTI^ESKIE DIFFERENCIALXNYE SISTEMY (B/s - (NpUGA^EW(B, (NwLADIMIR sEMENOWI^s; (NsINICYN(B, (NiGORX nIKOLAEWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1985)
(NbIBLIOGR(B.: (NS(B. 553-557 (101 (NNAZW(B.)s
(NpREDM(B. (NUKAZ(B.: (NS(B. 558-559s
Keywords: (NdIFFERENCIALXNYE URAWNENIQ STOHASTI^ESKIEs